Pemodelan Kecelakaan Sepeda Motor di Beberapa Ruas Jalan di Kota Surabaya Barat dengan Metode Generalized Linear Model - Bambang Harianto; Lasmini Ambarwati; Rahayu Kusumaningrum (Jurnal Mahasiswa Jurusan Teknik Sipil, 2025)
Traffic accidents, especially involving motorcycle users, are a major problem in Indonesia, with high fatality rates based on data from various studies and official reports. West Surabaya is an area with quite significant motorcycle accidents, so it is necessary to conduct an in-depth analysis of factors that can improve traffic safety. To determine the best strategy to reduce the number of motorcycle accidents, this study aims to form a motorcycle accident probability model in West Surabaya City based on geometric data and road traffic. General linear model (GLM) analysis is used to create this model based on geometric data and road traffic. This study found a significant correlation between traffic volume and speed to the level of motorcycle accidents. Motorcycle traffic accidents increase along with the increase in traffic flow on the roads reviewed around West Surabaya, and the speed that may increase. Every increase in speed value of one unit, motorcycle accidents will increase by a factor of e0.078 or equivalent to a multiplication of 1.0811.